Statin Treatment Is Associated With a Neutral Effect on Health-Related Quality of Life Among Community-Dwelling Octogenarian Men: The Helsinki Businessmen Study. (12th April 2018) - Strandberg, Timo E; Urtamo, Annele; Kähärä, Juuso; Strandberg, Arto Y; Pitkälä, Kaisu H; Kautiainen, Hannu
Abstract: Background: Statin treatment is common among 80+ people, but little is known about statin effects on health-related quality of life (HRQoL) in this oldest age group. Methods: In the Helsinki Businessmen Study (HBS), men born from 1919 to 1934 (original n = 3, 490), have been followed-up since the 1960s. In 2015, a questionnaire about lifestyle, diseases, and medications, and including RAND-36/SF-36 HRQoL instrument was mailed to survivors. About 612 men (72.6%) responded, 530 of them reporting their medications (98% community-living). Propensity score analysis was used to compare statin users and nonusers for HRQoL. Results: We compared 229 current statin users (median age 85 years, interquartile range 84–88 years) with 301 nonusers (86; 84–89 years). Current statin users had had significantly higher serum cholesterol level in midlife ( p < .001), but current lifestyle-related characteristics were similar in users and nonusers. Statin users reported more hypertension (61.1%, p < .001), diabetes (23.6%, p <.001), and atherosclerotic cardiovascular disease (ASCVD, 33.6%, p <.001), than nonusers. Statin users reported higher mean scores than nonusers in all eight RAND-36 subscales, but after adjustments for multiplicity and a propensity score we found no significant differences between statin users and nonusers. Stratification for primary (no ASCVD) and secondary (with CVD) prevention supported the main results. Conclusions: Our study suggests that statin treatment has no significant effect on health-related quality of life among octogenarian, community-dwelling men. The results contradict concerns about statin treatment in the oldest-old, and may caution against deprescribing of statins due to old age alone.